Long-term results by using cochlear Implants on children: Systematic review - Tanamati, Liège Franzini; Costa, Orozimbo Alves; Bevilacqua, Maria Cecilia (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Cochlear Implant (CI) benefits given to children in the first years of usage have been thoroughly described in literature. Nonetheless, studies reporting the results after the device has been long used are scarce.Objective: Review the available evidence in literature to answer the query: “Did Cochlear Implant effectively contribute to develop the communication abilities in children and young adults who grew up with this device?Method: To answer the suggested query, a systematic literature review was performed. Several electronic databases and congress records have been selected to find the evidence regarding the long-term CI results. The likely significant titles to answer the objective of the systematic review were retrieved and reviewed by using a data analysis protocol. For every article encompassed in the present systematic review, short notes were made on a filing card as well as the classification, according to evidence level and degree of recommendation.Data synthesis: Fifteen studies fulfilled the requirements and were included in the systematic review. The achieved results showed that the first generation of implanted children reached levels of linguistic and academic proficiency similar to normal hearing individuals at the same age.Final Comments: CI effectively contributed to develop the functional communication abilities in children and young adults who grew up with this electronic device.
Keywords: cochlear implant; evaluation of results (health care); follow-up studies